2016
DOI: 10.1007/s11738-016-2183-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response of cornflower (Centaurea cyanus L.) exposed to tribenuron-methyl: one of the active substances of sulfonylurea herbicides

Abstract: Tribenuron-methyl is the active substance of the herbicide used for weed control in crops. The aim of this study was to investigate differences in the metabolic response of seeds, seedlings and leaves of Centaurea cyanus L., depending on the degree of resistance to tribenuron-methyl. Changes in the values of selected biochemical and physiological parameters (germination index, chemical composition, photochemical efficiency of photosystem II and the emission spectra of blue-green fluorescence) presented herein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…These evidences showed that severe destruction of rapeseed photosynthesis system and abnormal regulation of cell cycle related genes, and induction of autophagy in anther cells were associated with the CIMS. Although the relationships among ALS protein function and photosynthesis system and cell cycle are not known, the available data in our studies and previous literatures (Rost et al, 1990 ; Qian et al, 2011 ; Cheng et al, 2013 ; Li et al, 2015 ; Saja et al, 2016 ; Sun et al, 2016 ) suggested that disruption of photosynthesis and inhibition of cell cycle are two major phytotoxic effects of amidosulfuron. Down-regulation of some genes about carbohydrate metabolism and sugar transporter also intimated a possible disruption of photoassimilate translocation.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…These evidences showed that severe destruction of rapeseed photosynthesis system and abnormal regulation of cell cycle related genes, and induction of autophagy in anther cells were associated with the CIMS. Although the relationships among ALS protein function and photosynthesis system and cell cycle are not known, the available data in our studies and previous literatures (Rost et al, 1990 ; Qian et al, 2011 ; Cheng et al, 2013 ; Li et al, 2015 ; Saja et al, 2016 ; Sun et al, 2016 ) suggested that disruption of photosynthesis and inhibition of cell cycle are two major phytotoxic effects of amidosulfuron. Down-regulation of some genes about carbohydrate metabolism and sugar transporter also intimated a possible disruption of photoassimilate translocation.…”
Section: Discussionsupporting
confidence: 43%
“…Ethylene is commonly associated with cell death, restricting cell elongation and regulation of cell division (Rogers, 2013 ). Some previous evidences suggested that valine, leucine and isoleucine may be involved in the regulation of cell division (Rost et al, 1990 ) and sulfonylurea herbicides disturbed cell division in the meristematic tissues of plants (Saja et al, 2016 ). We also found that amidosulfuron can restrain the raceme elongation (cell growth) in the first days after treatment and the pollen development was terminated before microspore mitosis (the flower bud length of 3–3.5 mm), as various sulfonylurea herbicides did in different cultivars (Yu et al, 2006 , 2009 , 2017 ; Yu and He, 2014 ; Li et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SU herbicides may damage the photosynthetic apparatus [33] because plant ALS proteins are located in plastids and chloroplasts [34]. We found that the photosynthetic rate and chlorophyll content were obviously affected in the several days after the sub-lethal dose of the TBM treatment, similar to the effects of another gametocide amidosulfuron [10].…”
Section: Discussionmentioning
confidence: 79%